Pericytes from human veins for treatment of myocardial ischemia - Katare, Rajesh G. (2013)
Stem cell therapies promise to regenerate the infarcted heart through the replacement of dead cardiac cells and stimulation of neovascularization. New research from our laboratory shows the transplantation of stem cells from human veins helps heart healing after an acute ischemic insult. Using a mouse model, we demonstrated that pericytes expanded from redundant human leg veins relocate around the vessels of the peri-infarct zone and release factors that promote reparative angiogenesis and cardiomyocyte survival and inhibit interstitial fibrosis. We plan to perform a first-in-man clinical trial with human pericytes in patients with refractory myocardial ischemia in the next 5 years.